Les droits du cessionnaire à l'égard de la compagnie : « mandamus » et transfert d'actions - Demers, Robert (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1979)
This commentary deals with the recourse available to a transferee of shares when the corporation refuses to execute the transfer in its books. The application of mandamus in such a context is examined as are various restrictions on transfer contained in shareholders' agreements. The power of directors to refuse to register a transfer must be founded on a proper motive and where the court finds an impropriety at this level, it may enjoin registration by the issuance of a mandamus or an injunction.